2015
DOI: 10.4137/cmped.s21426
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Dysfunction in Asphyxiated Neonates: Prospective Case-Controlled Study

Abstract: OBJECTIVEThis study was performed to determine the occurrence of hypoxic hepatitis in full-term neonates after perinatal asphyxia and to correlate between the rise in enzymes and severity of asphyxia with Apgar score and hypoxic ischemic encephalopathy (HIE) grading of the neonates.METHOD AND MATERIALThis prospective case-controlled study was conducted in a tertiary-level hospital in India for a period of 12 months. The study group A comprised 70 newborns suffering from birth asphyxia, while 30 healthy neonate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
46
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(60 citation statements)
references
References 11 publications
(17 reference statements)
12
46
0
1
Order By: Relevance
“…This study is similar to the findings observed by Mukesh Choudhary, [7] Tariqul I et al [33] and Chaitali Patra et al [34] The Table 9 depicts that 2 babies from HIE-2 group died, one within 1 -3 days and the other one within 4 -7 days.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…This study is similar to the findings observed by Mukesh Choudhary, [7] Tariqul I et al [33] and Chaitali Patra et al [34] The Table 9 depicts that 2 babies from HIE-2 group died, one within 1 -3 days and the other one within 4 -7 days.…”
Section: Discussionsupporting
confidence: 81%
“…Chiabi A and Nguefack S et al (2013) [10] that out of total number of asphyxiated babies 51% were HIE-1, 26% were HIE-2 and 23% were HIE-3. Mukesh Choudhary et al (2015) [7] in their study observed 14.28% were HIE-1; 25.73% were HIE-2; 11.42% were HIE-3. Hassan Boskabadi et al (2015) [11] in their study found HIE-1 were 11.86%; HIE-2 were 45.76%; HIE-3 were 42.37%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Renal dysfunction due to acute tubular necrosis is usually transient and resolves in the first week [51]. Liver damage manifests as elevated transaminases and may exacerbate coagulation problems [52]. Early aggressive enteral feeding should be avoided as this may precipitate necrotizing enterocolitis [53].…”
Section: Ventilation and Oxygenationmentioning
confidence: 99%